High field imaging of large-scale neurotransmitter networks: Proof of concept and initial application to epilepsy - Tamar M. van Veenendaal; Walter H. Backes; Desmond H.Y. Tse; Tom W.J. Scheenen; Dennis W. Klomp; Paul A.M. Hofman; Rob P.W. Rouhl; Marielle C.G. Vlooswijk; Albert P. Aldenkamp; Jacobus F.A. Jansen (NeuroImage: Clinical, 2018)
The brain can be considered a network, existing of multiple interconnected areas with various functions. MRI provides opportunities to map the large-scale network organization of the brain. We tap into the neurobiochemical dimension of these networks, as neuronal functioning and signal trafficking across distributed brain regions relies on the release and presence of neurotransmitters. Using high-field MR spectroscopic imaging at 7.0 T, we obtained a non-invasive snapshot of the spatial distribution of the neurotransmitters GABA and glutamate, and investigated interregional associations of these neurotransmitters. We demonstrate that interregional correlations of glutamate and GABA concentrations can be conceptualized as networks. Furthermore, patients with epilepsy display an increased number of glutamate and GABA connections and increased average strength of the GABA network. The increased glutamate and GABA connectivity in epilepsy might indicate a disrupted neurotransmitter balance. In addition to epilepsy, the ‘neurotransmitter networks’ concept might also provide new insights for other neurological diseases. Keywords: GABA, Glutamate, MR spectroscopic imaging, Networks, 7T